Alteration in redox profile in multiple sclerosis patients (Research, Society and Development, 2021)
Multiple sclerosis is a neurodegenerative, chronic and autoimmune disease that affects the central nervous system, characterized by the demyelination of neurons preventing nerve impulses from reaching the intended areas. Oxidative stress is an imbalance between the antioxidant defense system and the reactive species present in the body. Both are related in some way that is not yet elucidated. In view of this, the objective was to evaluate the redox profile of patients with multiple sclerosis by making a comparison with healthy individuals. This study was accepted by the Research Ethics Committee of the University of Cruz Alta under the number: 3,531,405. Participated in the study 10 patients with multiple sclerosis, group (EM) and 8 healthy individuals, control group (CT) both groups signed the Free and Informed Consent Form. For analysis, blood samples were collected, which were processed and the plasma was removed. The analyzes were performed according to techniques described in the literature. The results were analyzed using the Mann-Whitney test, considering statistically significant p